PHARMACOLOGICAL PRECONDITIONING BY RECOMBINANT ERYTHROPOIETIN AS THE POSSIBILITY OF INCREASING THE STABILITY OF TISSUE OF THE RETINA TO REPERFUSION ISCHEMIA IN EXPERIMENT - Anna Shabelnikova; Anna Peresypkina; Viktoriya Gubareva; Elena Levkova; Alexandr Dolzhikov; Sergej Nikolaev; Aleksandr Stepchenko (Belgorod National Research University, 2016)
Ischemic injury was formed in laboratory rats by applying mechanical pressure (110 mm Hg) to the anterior eye chamber for 30 minutes. The experiment revealed that the recombinant erythropoietin (50 IU/kg) prevents the development of degenerative changes in retinal layers caused by ischemic injury. Intensity of the protective effect of erythropoietin on the retina of rats was assessed after 1 hour and 72 hours of reperfusion after pathology simulation. The observed protective effect of erythropoietin with the development of ischemia was confirmed by laser Doppler flowmetry, electroretinography and histomorphometry. Identification and use of pharmacological agents with the preconditioning effect may be a new approach in the correction and prevention of retinal ischemia, which is the leading element in the pathogenesis of a number of ophtalmic pathologies. The possibility of pharmacological preconditioning of ischemic lesions of the retina with erythropoietin is essential for the development of anti-ischemic agents for the treatment and prevention of ischemic ophthalmic pathologies.